2009
DOI: 10.7589/0090-3558-45.3.661
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molt on Plasma Protein Electrophoretic Patterns in Bar-Headed Geese (Anser Indicus)

Abstract: ABSTRACT:Plasma protein electrophoresis is recognized as a reliable diagnostic tool in avian medicine; however, the influence of circannual phenomena such as molt on protein electrophoregrams is poorly documented. The molt is a period of heavy hormonal and metabolic change in birds. The purpose of this study was to investigate the effects of molt on total protein concentration and electrophoresis patterns in birds. Blood samples were taken from 19 Barheaded Geese (Anser indicus) from mid-May to mid-August, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The fattening period of broiler chickens is very short, and there is a rapid accumulation of building proteins in the body tissues, which may significantly influence the concentrations of proteins in the blood, as well as their composition [ 65 ]. This rapid growth trend requires intensive erythropoiesis and haemoglobin synthesis, which can result in increased globulin production, potentially affecting the concentrations of serum protein levels in growing chickens [ 66 , 67 ]. The current study results showed that the inclusion of POLM significantly increased the levels of TP, albumin, and globulin compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The fattening period of broiler chickens is very short, and there is a rapid accumulation of building proteins in the body tissues, which may significantly influence the concentrations of proteins in the blood, as well as their composition [ 65 ]. This rapid growth trend requires intensive erythropoiesis and haemoglobin synthesis, which can result in increased globulin production, potentially affecting the concentrations of serum protein levels in growing chickens [ 66 , 67 ]. The current study results showed that the inclusion of POLM significantly increased the levels of TP, albumin, and globulin compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Among various pathological conditions causing changes in the serum biochemistry values, there are several physiological (breeding, molting, and nest building), as well as exogenous factors (husbandry conditions), that may potentially affect the concentrations of serum proteins also in birds [7,8]. The process of growth and development in chickens, especially in broilers, is a very intensive period accompanied by great metabolic changes, increase of body mass, and accumulation of enormous amount of muscle in a very short time [9].…”
Section: Introductionmentioning
confidence: 99%
“…This initial rise was followed by a decrease over the next stages of moult, similarly as in our study. A decrease in total protein concentration during moult was also recorded in seabirds (Work, 1996), passerines (Newton, 1968; DeGraw & Kern, 1985), ducks and geese (Driver, 1981; Roman et al, 2009). Other studies showed that the level of total protein was significantly higher after moult than during feather replacement (Thompson & Drobney, 1996).…”
Section: Discussionmentioning
confidence: 83%
“…Snipe have probably the highest protein demand at the beginning of moult, due to the rapid acceleration of keratin synthesis for feather production and other metabolic processes associated with early phases of moult, such as vascularization of the active feather follicles, pulp formation, and an increase of erythrocytes (DeGraw & Kern, 1985; Murphy & King, 1992). It has been shown that deposition of protein as keratins of feathers may equal a quarter or more of the total protein mass of the bird (Newton, 1968; Murphy & Taruscio, 1995; Roman et al, 2009). Production of keratin depends largely upon sulphur containing amino acids (cysteine and cystine), which, thus, may be critical for plumage synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation